Physicochemical, functional, and sensory characteristics of spray-dried instant Minasarua: a functional beverage - Neyla Vista Maramy; Tri Dewanti Widyaningsih; Erryana Martati; Agustina Tri Endharti; Safira Salsabila (CyTA - Journal of Food, 2025)
Minasarua, a traditional Indonesian beverage, is rich in bioactive compounds and has functional properties for health, but it has a short shelf life. Spray drying is a method to make an instant product with an extended shelf life. This research investigated the effect of combining maltodextrin concentration (5% and 10%) and spray drying inlet temperature (160°C, 190°C, and 220°C) on the physicochemical, functional, and sensory properties of instant Minasarua. The treatment with 10% maltodextrin and 220°C spray drying inlet temperature resulted in an instant Minasarua, which is preferable to other treatments. This treatment had low moisture content (0.97%), less wettability time (79.25 sec), low bulk density (0.35 g/mL), and significant antioxidant activity (7.93 mg TE/g). Additionally, other physicochemical and sensory properties showed considerable results. These findings potentially improve the shelf life and health benefits of Minasarua, making it more accessible and advantageous to a broader population.